Ethylene Polymerization over MgCl2/SiO2 Bi‐Supported Ziegler–Natta Hybrid Titanium/Vanadium Catalysts. Issue 13 (28th April 2017) - Fu, Ting; Liu, Zhen; Cheng, Ruihua; He, Xuelian; Tian, Zhou; Liu, Boping
Abstract : MgCl2 /SiO2 bi‐supported Ziegler–Natta hybrid titanium/vanadium catalysts are synthesized with magnesium acetate as Mg source under different reaction sequences with TiCl4 and VOCl3 . The one‐step co‐reaction with TiCl4 and VOCl3 is better than the two‐step reaction method for the hybrid catalyst system in catalytic activity, hydrogen response, and 1‐hexene incorporation. Abstract : MgCl2 /SiO2 bi‐supported Ziegler–Natta hybrid titanium/vanadium catalysts are synthesized with magnesium acetate as Mg source under different reaction sequences with TiCl4 and VOCl3 . The activities of Ti/V hybrid catalysts are almost between those of MgTi/Si and MgV/Si catalysts. The hybrid titanium/vanadium catalyst prepared by coreaction with TiCl4 and VOCl3 shows higher activity than those prepared via two‐step reaction method. Regarding kinetic curves of ethylene polymerization, comonomer effect, and polymer properties, hybrid catalysts prepared through two‐step reaction method are inclined to exhibit more traits of the second active species supported during catalyst preparation. The vanadium species can adjust the molecular weight of polymers more efficiently by adding hydrogen with the sacrifice of catalytic activity for MgTiV/Si and MgTi‐V/Si catalysts. The one‐step coreaction method is more advantageous in catalytic activity, hydrogen response, and 1‐hexene incorporation than the two‐step reaction method for the MgCl2 /SiO2 bi‐supported Ziegler–Natta hybrid titanium/vanadium catalyst system.